Aripiprazole for acute mania in an elderly person - Bharadwaj, Balaji (Medknow Publications & Media Pvt Ltd, 2011)
New-onset bipolar disorder is rare in the elderly. Symptom profile is similar to that in young adults but the elderly are more likely to have neurological co-morbidities. There are no case reports of elderly mania being treated with aripiprazole, an atypical antipsychotic. A 78-year-old gentleman presented to us with symptoms suggestive of mania of 1 month's duration. He had similar history 3 years ago and a family history of postpartum psychosis in his mother. There were no neurological signs on examination and work-up for an organic etiology was negative except for age-related cerebral atrophy. He improved with aripiprazole and tolerated the medications well. The use of psychotropic medications in the elderly is associated with side-effects of sedation, increased cardiovascular risk, and greater risk of extra-pyramidal side-effects. The use of partial dopaminergic antagonists like aripiprazole may be useful in the balancing of effects and side-effects.